Assessing the Role of Education on Intergenerational Income Mobility: The Case of Indonesia - Kawinata, Michelle; Djohan, Stephanie; Kadarusman, Yohanes B.; Desfiandi, Alvin (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2022)
This paper aims to address the role of education in Indonesia’s intergenerational income mobility. This will include measuring the level of intergenerational mobility to establish the general condition in Indonesia through the estimation of intergenerational income mobility. The main data used to test the model will be secondary data from the Indonesian Family Life Survey in 1993, 1997, 2000, 2007 and 2014. Through multiple linear regression analysis, the authors conclude that education influences the levels of intergenerational income mobility in Indonesia. Child’s education has a larger coefficient than father’s education in determining the child’s income. Public policy must focus on human investment to develop human capital through a provision of quality education throughout the country, particularly for people from lower income groups. Indonesia’s government should also allocate its education spending to increase the attainment of higher education level, establishing the next generations with higher productivity and income than previous generations.